2015
DOI: 10.1245/s10434-015-4968-3
|View full text |Cite
|
Sign up to set email alerts
|

Results of a Randomized Controlled Multicenter Phase III Trial of Percutaneous Hepatic Perfusion Compared with Best Available Care for Patients with Melanoma Liver Metastases

Abstract: This randomized, phase III study demonstrated the efficacy of the PHP-Mel procedure. hPFS, oPFS, and hOR were significantly improved with PHP-Mel. PHP with melphalan should provide a new treatment option for unresectable metastatic melanoma in the liver.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

20
127
1
13

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 127 publications
(161 citation statements)
references
References 24 publications
20
127
1
13
Order By: Relevance
“…During recent years, different treatment approaches have been tested in patients with metastatic UM. Responses have been reported mainly with localized treatment in patients with a limited number of metastases in the liver [2][3][4][5][6]. When diffuse liver involvement and/or extrahepatic disease have developed, systemic therapies are warranted.…”
mentioning
confidence: 99%
“…During recent years, different treatment approaches have been tested in patients with metastatic UM. Responses have been reported mainly with localized treatment in patients with a limited number of metastases in the liver [2][3][4][5][6]. When diffuse liver involvement and/or extrahepatic disease have developed, systemic therapies are warranted.…”
mentioning
confidence: 99%
“…Some fatalities were observed on this trial and each death lead to further safety maneuvers in the development of improved filters. [15,16] The authors concluded that the results of their phase III study demonstrate the efficacy of PHP-Mel. They report that the toxicity is significant but manageable in order to provide effective therapy for this select cohort of patients.…”
Section: Phase III Multicenter Trialmentioning
confidence: 99%
“…Hughes et al [16] published results of the phase III, multicenter randomized trial comparing PHP with melphalan (PHP-Mel) to best alternative care (BAC) for patients with cutaneous or ocular melanoma metastatic to the liver. The trial accrued 93 patients between February 2006 and July 2009.…”
Section: Phase III Multicenter Trialmentioning
confidence: 99%
See 2 more Smart Citations